BACE1 modulates gating of KCNQ1 (Kv7.1) and cardiac delayed rectifier KCNQ1/KCNE1 (IKs) - Agsten, Marianne; Heßler, Sabine; Lehnert, Sandra; Volk, Tilmann; Rittger, Andrea; Hartmann, Stephanie; Raab, Christian; Kim, Doo Yeon; Groemer, Teja W.; Schwake, Michael; Alzheimer, Christian; Huth, Tobias (Journal of Molecular and Cellular Cardiology, 2015)
KCNQ1 (Kv7.1) proteins form a homotetrameric channel, which produces a voltage-dependent K(+) current. Co-assembly of KCNQ1 with the auxiliary ?-subunit KCNE1 strongly up-regulates this current. In cardiac myocytes, KCNQ1/E1 complexes are thought to give rise to the delayed rectifier current IKs, which contributes to cardiac action potential repolarization. We report here that the type I membrane protein BACE1 (?-site APP-cleaving enzyme 1), which is best known for its detrimental role in Alzheimer's disease, but is also, as reported here, present in cardiac myocytes, serves as a novel interaction partner of KCNQ1. Using HEK293T cells as heterologous expression system to study the electrophysiological effects of BACE1 and KCNE1 on KCNQ1 in different combinations, our main findings were the following: (1) BACE1 slowed the inactivation of KCNQ1 current producing an increased initial response to depolarizing voltage steps. (2) Activation kinetics of KCNQ1/E1 currents were significantly slowed in the presence of co-expressed BACE1. (3) BACE1 impaired reconstituted cardiac IKs when cardiac action potentials were used as voltage commands, but interestingly augmented the IKs of ATP-deprived cells, suggesting that the effect of BACE1 depends on the metabolic state of the cell. (4) The electrophysiological effects of BACE1 on KCNQ1 reported here were independent of its enzymatic activity, as they were preserved when the proteolytically inactive variant BACE1 D289N was co-transfected in lieu of BACE1 or when BACE1-expressing cells were treated with the BACE1-inhibiting compound C3. (5) Co-immunoprecipitation and fluorescence recovery after photobleaching (FRAP) supported our hypothesis that BACE1 modifies the biophysical properties of IKs by physically interacting with KCNQ1 in a ?-subunit-like fashion. Strongly underscoring the functional significance of this interaction, we detected BACE1 in human iPSC-derived cardiomyocytes and murine cardiac tissue and observed decreased IKs in atrial cardiomyocytes of BACE1-deficient mice.
EVALuna2:2471

Cold storage of mouse hearts prior to cardiomyocyte isolation preserves electromechanical function, microstructure, and gene expression for 24 h - Pfeilschifter, Benedikt; Martinez-Vilchez, Aiora; Iqbal, Zafar; Potue, Prapassorn; Fiegle, Dominik; Morhenn, Karoline; Schwoerer, Alexander P.; Volk, Tilmann; Seidel, Thomas (Basic research in cardiology, 2025)
Isolation of myocytes from mouse hearts, especially of transgenic animals or disease models, is crucial in cardiac research. The presumption that cardiomyocytes must be isolated immediately after heart procurement to avoid deterioration implies that transgenic mouse lines must be present on site, causes schedule inflexibility, and hampers collaborations, thereby increasing the number, suffering, and costs of animals. This study challenges this presumption by investigating whether the cell isolation can be postponed for 24 h without affecting the results. Adult mouse hearts were subjected to enzymatic myocyte isolation immediately after excision (CTRL) or after 24 h of cold storage (CS). Sufficient numbers of viable cardiomyocytes were obtained in all groups. The transverse-axial tubular system was unchanged in CS versus CTRL. No significant changes were detected in cell capacitance, resting membrane potential, action potential shape and duration, amplitudes, and kinetics of the K+ currents Ito, IK1, and IK. Sarcomere length, contractility, and relaxation as well as Ca2+ signals were equivalent in CS and CTRL at pacing rates of 1–4 Hz. Mitochondrial function assays also yielded equivalence. RNA sequencing yielded only 128 differentially expressed genes, which were mainly related to immune cell function and inflammation. Key findings were reproduced in infarcted mouse hearts, which were shipped overnight as a proof of principle. This study demonstrates that the isolation of cardiomyocytes can be postponed up to 24 h after the procurement of the heart. This opens up new possibilities for collaboration between different laboratories, increases experimental flexibility, and allows to reduce the number of experimental animals by avoiding unnecessary propagation of transgenic lines.
CRIS-Team Scopus Importer:2025-08-08
Keywords: Excitation–contraction coupling; Gene expression; Heart conservation; Ischemia; Reduction of animals

Corrigendum: long-term cultivation of human atrial myocardium (Frontiers in Physiology, (2022), 13, (839139), 10.3389/fphys.2022.839139) - Klumm, Maximilian J. J.; Heim, Christian; Fiegle, Dominik; Weyand, Michael; Volk, Tilmann; Seidel, Thomas (Frontiers in Physiology, 2023)
In the published article, there was an error in Author Contributions. The following sentence was missing. MK performed this work in (partial) fulfillment of the requirements for obtaining the degree “Dr. med.”. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
CRIS-Team Scopus Importer:2023-06-02
Keywords: calcium imaging; confocal microscopy; gene expression; human atrium; in vitro; refractory period; tissue culture

Corticosteroids and insulin upregulate the cardiac L-type Ca2+ current and increase the expression of the L-type Ca2+ channel alpha C-1-subunit in rat cardiomyocytes - Rudakova, Elena; Wagner, Michael; Volk, Tilmann (2016)
EVALuna2:214664

Developing a patient individualized flexible silicone implant using SLS and vacuum die casting - Launhardt, Martin; Ebel, Nina; Kondruweit, Markus; Weyand, Michael; Volk, Tilmann; Drummer, Dietmar (AIP Conference Proceedings, 2019)

Developing a Patient Individualized Flexible Silicone Implant using SLS and Vacuum Die Casting - Launhardt, Martin; Ebel, Nina; Kondruweit, Markus; Weyane, Michael; Volk, Tilmann; Drummer, Dietmar (PROCEEDINGS OF THE EUROPE/AFRICA CONFERENCE DRESDEN 2017 - POLYMER PROCESSING SOCIETY PPS, 2019)
CRIS-Team WoS Importer:2019-05-03

Dexamethasone prevents loss of T-tubules in primary cultured adult rat cardiomyocytes - Seidel, Thomas; Baur, T.; Volk, Tilmann (2017)
EVALuna2:214663

Effects of electro-mechanical uncouplers, hormonal stimulation and pacing rate on the stability and function of cultured rabbit myocardial slices - Baron, V.; Sommer, Sophie; Fiegle, Dominik; Pfeuffer, Ann-Katrin; Peyronnet, R.; Volk, Tilmann; Seidel, Thomas (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Recent advances have enabled organotypic culture of beating human myocardial slices that are stable for weeks. However, human myocardial samples are rare, exhibit high variability and frequently originate from diseased hearts. Thus, there is a need to adapt long-term slice culture for animal myocardium. When applied to animal cardiac slices, studies in healthy or genetically modified myocardium will be possible. We present the culture of slices from rabbit hearts, which resemble the human heart in microstructure, electrophysiology and excitation-contraction coupling. Methods: Left ventricular myocardium from New Zealand White rabbits was cut using a vibratome and cultured in biomimetic chambers for up to 7 days (d). Electro-mechanical uncoupling agents 2,3-butanedione monoxime (BDM) and cytochalasin D (CytoD) were added during initiation of culture and effects on myocyte survival were quantified. We investigated pacing rates (0.5 Hz, 1 Hz, and 2 Hz) and hormonal supplements (cortisol, T3, catecholamines) at physiological plasma concentrations. T3 was buffered using BSA. Contractile force was recorded continuously. Glucose consumption and lactate production were measured. Whole-slice Ca2+ transients and action potentials were recorded. Effects of culture on microstructure were investigated with confocal microscopy and image analysis. Results: Protocols for human myocardial culture resulted in sustained contracture and myocyte death in rabbit slices within 24 h, which could be prevented by transient application of a combination of BDM and CytoD. Cortisol stabilized contraction amplitude and kinetics in culture. T3 and catecholaminergic stimulation did not further improve stability. T3 and higher pacing rates increased metabolic rate and lactate production. T3 stabilized the response to β-adrenergic stimulation over 7 d. Pacing rates above 1 Hz resulted in progredient decline in contraction force. Image analysis revealed no changes in volume fractions of cardiomyocytes or measures of fibrosis over 7 d. Ca2+ transient amplitudes and responsiveness to isoprenaline were comparable after 1 d and 7 d, while Ca2+ transient duration was prolonged after 7 d in culture. Conclusions: A workflow for rabbit myocardial culture has been established, preserving function for up to 7 d. This research underscores the importance of glucocorticoid signaling in maintaining tissue function and extending culture duration. Furthermore, BDM and CytoD appear to protect from tissue damage during the initiation phase of tissue culture.
CRIS-Team Scopus Importer:2024-05-10
Keywords: biomimetic chambers; contractility; multicellular preparations; organotypic culture; reperfusion injury

Glucocorticoid signaling and modulation of autophagy is involved in the preservation of the cardiomyocyte t-tubular system - Fiegle, Dominik; Abu-Khousa, M.; Seidel, Thomas; Volk, Tilmann (ACTA PHYSIOLOGICA, 2019)
CRIS-Team WoS Importer:2019-11-12

Glucocorticoids preserve the t-tubular system in ventricular cardiomyocytes by upregulation of autophagic flux - Seidel, Thomas; Fiegle, Dominik; Baur, Tim J.; Ritzer, Anne; Nay, Sandra; Heim, Christian; Weyand, Michael; Milting, Hendrik; Oakley, Robert H.; Cidlowski, John A.; Volk, Tilmann (Basic Research in Cardiology, 2019)
A major contributor to contractile dysfunction in heart failure is remodelling and loss of the cardiomyocyte transverse tubular system (t-system), but underlying mechanisms and signalling pathways remain elusive. It has been shown that dexamethasone promotes t-tubule development in stem cell-derived cardiomyocytes and that cardiomyocyte-specific glucocorticoid receptor (GR) knockout (GRKO) leads to heart failure. Here, we studied if the t-system is altered in GRKO hearts and if GR signalling is required for t-system preservation in adult cardiomyocytes. Confocal and 3D STED microscopy of myocardium from cardiomyocyte-specific GRKO mice revealed decreased t-system density and increased distances between ryanodine receptors (RyR) and L-type Ca2+ channels (LTCC). Because t-system remodelling and heart failure are intertwined, we investigated the underlying mechanisms in vitro. Ventricular cardiomyocytes from failing human and healthy adult rat hearts cultured in the absence of glucocorticoids (CTRL) showed distinctively lower t-system density than cells treated with dexamethasone (EC50 1.1 nM) or corticosterone. The GR antagonist mifepristone abrogated the effect of dexamethasone. Dexamethasone improved RyR–LTCC coupling and synchrony of intracellular Ca2+ release, but did not alter expression levels of t-system-associated proteins junctophilin-2 (JPH2), bridging integrator-1 (BIN1) or caveolin-3 (CAV3). Rather, dexamethasone upregulated LC3B and increased autophagic flux. The broad-spectrum protein kinase inhibitor staurosporine prevented dexamethasone-induced upregulation of autophagy and t-system preservation, and autophagy inhibitors bafilomycin A and chloroquine accelerated t-system loss. Conversely, induction of autophagy by rapamycin or amino acid starvation preserved the t-system. These findings suggest that GR signalling and autophagy are critically involved in t-system preservation and remodelling in the heart.
CRIS-Team Scopus Importer:2019-11-08
Keywords: Autophagy; Calcium signalling; Excitation–contraction coupling; Glucocorticoid receptor; Heart failure; Remodelling; Transverse tubular system

Isolation of human ventricular cardiomyocytes from vibratome-cut myocardial slices - Fiegle, Dominik; Volk, Tilmann; Seidel, Thomas (Journal of Visualized Experiments, 2020)
The isolation of ventricular cardiac myocytes from animal and human hearts is a fundamental method in cardiac research. Animal cardiomyocytes are commonly isolated by coronary perfusion with digestive enzymes. However, isolating human cardiomyocytes is challenging because human myocardial specimens usually do not allow for coronary perfusion, and alternative isolation protocols result in poor yields of viable cells. In addition, human myocardial specimens are rare and only regularly available at institutions with on-site cardiac surgery. This hampers the translation of findings from animal to human cardiomyocytes. Described here is a reliable protocol that enables efficient isolation of ventricular myocytes from human and animal myocardium. To increase the surface-to-volume ratio while minimizing cell damage, myocardial tissue slices 300 µm thick are generated from myocardial specimens with a vibratome. Tissue slices are then digested with protease and collagenase. Rat myocardium was used to establish the protocol and quantify yields of viable, calcium-tolerant myocytes by flow-cytometric cell counting. Comparison with the commonly used tissue-chunk method showed significantly higher yields of rod-shaped cardiomyocytes (41.5 ± 11.9 vs. 7.89 ± 3.6%, p < 0.05). The protocol was translated to failing and non-failing human myocardium, where yields were similar as in rat myocardium and, again, markedly higher than with the tissue-chunk method (45.0 ± 15.0 vs. 6.87 ± 5.23 cells/mg, p < 0.05). Notably, with the protocol presented it is possible to isolate reasonable numbers of viable human cardiomyocytes (9–200 cells/mg) from minimal amounts of tissue (<50 mg). Thus, the method is applicable to healthy and failing myocardium from both human and animal hearts. Furthermore, it is possible to isolate excitable and contractile myocytes from human tissue specimens stored for up to 36 h in cold cardioplegic solution, rendering the method particularly useful for laboratories at institutions without on-site cardiac surgery.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Biology; Calcium imaging; Cardiac excitation-contraction coupling; Cardiomyocyte isolation; Contractile myocytes; Heart failure; Human; Issue 159; Myocardial slices; Vibratome

Lipid Emulsion Increases the Fast Na+ Current and Reverses the Bupivacaine-induced Block: A New Aspect of Lipid Resuscitation? Reply - Wagner, Michael; Zausig, York A.; Ruf, Stefan; Rudakova, Elena; Gruber, Michael; Graf, Bernhard M.; Volk, Tilmann (Anesthesiology, 2014)
EVALuna2:4520

Lipid rescue reverses the bupivacaine-induced block of the fast Na+ current (INa) in cardiomyocytes of the rat left ventricle - Wagner, Michael; Zausig, York A.; Ruf, Simone; Rudakova, Elena; Gruber, Michael; Graf, Bernhard M.; Volk, Tilmann (Anesthesiology, 2014)
Cardiovascular resuscitation upon intoxication with lipophilic ion channel-blocking agents has proven most difficult. Recently, favorable results have been reported when lipid rescue therapy is performed, i.e., the infusion of a triglyceride-rich lipid emulsion during resuscitation. However, the mechanism of action is poorly understood.The authors investigate the effects of a clinically used lipid emulsion (Lipovenös® MCT 20%; Fresenius Kabi AG, Bad Homburg, Germany) on the block of the fast Na current (INa) induced by the lipophilic local anesthetic bupivacaine in adult rat left ventricular myocytes by using the whole cell patch clamp technique.Bupivacaine at 10 µm decreased INa by 54% (-19.3 ± 1.9 pApF vs. -42.3 ± 4.3 pApF; n = 17; P < 0.001; VPip = -40 mV, 1 Hz). Addition of 10% lipid emulsion in the presence of bupivacaine produced a 37% increase in INa (-26.4 ± 2.8 pApF; n = 17; P < 0.001 vs. bupivacaine alone). To test whether these results could be explained by a reduction in the free bupivacaine concentration by the lipid (lipid-sink effect), the authors removed the lipid phase from the bupivacaine-lipid mixture by ultracentrifugation. Also, the resulting water phase led to an increase in INa (+19%; n = 17; P < 0.001 vs. bupivacaine), demonstrating that part of the bupivacaine had been removed during ultracentrifugation. The substantially less lipophilic mepivacaine (40 µm) reduced INa by 27% (n = 24; P < 0.001). The mepivacaine-lipid mixture caused a significant increase in INa (+17%; n = 24; P < 0.001). For mepivacaine, only a small lipid-sink effect could be demonstrated (+8%; n = 23; P < 0.01), reflecting its poor lipid solubility.The authors demonstrate lipid rescue on the single-cell level and provide evidence for a lipid-sink mechanism.
EVALuna2:4497

Localization of Kv4.2 and KChIP2 in lipid rafts and modulation of outward K+ currents by membrane cholesterol content in rat left ventricular myocytes - Rudakova, Elena; Wagner, Michael; Frank, Magdalena; Volk, Tilmann (Pflügers Archiv: European Journal of Physiology, 2015)
Lipid rafts are cholesterol-enriched microdomains of the cell membrane. Here we investigate the localization of the pore forming K(+)-channel ?-subunit Kv4.2 and the ?-subunit KChIP2, underlying the transient outward K(+) current (I to), in lipid rafts in left ventricular myocytes. Furthermore, we explored the impact of membrane cholesterol depletion (using 20 mM methyl-beta-cyclodextrin (MBCD)) on K(+) outward currents. Cholesterol-saturated MBCD (20 mM) served as control. Myocytes were isolated from the left ventricular free wall of Wistar rats. The Triton X-100 (4 °C) insoluble fraction of whole cell protein was analyzed by sucrose density gradient centrifugation followed by Western blot. Kv4.2 and KChIP2 were partially detected in low-density fractions (lipid rafts). MBCD treatment (5 min) resulted in a shift of Kv4.2 and KChIP2 towards high-density fractions. K(+) currents were assessed by whole-cell patch-clamp. MBCD treatment resulted in a 29 ± 3 % decrease in I to (20.0 ± 1.6pApF(-1) vs. 28.5 ± 2.0pApF(-1), n = 15, p < 0.001, V Pip = 40 mV) within 5 min. Control solution resulted in a significantly smaller reduction in I to (17 ± 3 %, p < 0.001, p < 0.01 compared with MBCD). MBCD induced a 38 ± 9 % increase in the non-inactivating current component (I sus) (10.1 ± 0.6pApF(-1) vs. 7.6 ± 0.4pApF(-1), n = 15, p < 0.001). This effect was absent in control solution. The increase in I sus was not sensitive to 100 ?M 4-aminopyridine or 20 mM tetraethylammonium, making a contribution of Kv1.5 or Kv2.1 unlikely. In conclusion, in rat ventricular cardiomyocytes, a fraction of Kv4.2 and KChIP2 is localized in lipid rafts. Membrane cholesterol depletion results in 12 % net reduction of I to, a redistribution of the channel proteins Kv4.2 and KChIP2 and an increased delayed rectifier current.
EVALuna2:4522

Long-Term Cultivation of Human Atrial Myocardium - Klumm, Maximilian J.; Heim, Christian; Fiegle, Dominik; Weyand, Michael; Volk, Tilmann; Seidel, Thomas (Frontiers in Physiology, 2022)
Organotypic culture of human ventricular myocardium is emerging in basic and translational cardiac research. However, few institutions have access to human ventricular tissue, whereas atrial tissue is more commonly available and important for studying atrial physiology. This study presents a method for long-term cultivation of beating human atrial myocardium. After written informed consent, tissues from the right-atrial appendage were obtained from patients with sinus rhythm undergoing open heart surgery with cardiopulmonary bypass. Trabeculae (pectinate muscles) prepared from the samples were installed into cultivation chambers at 37°C with a diastolic preload of 500 μN. After 2 days with 0.5 Hz pacing, stimulation frequency was set to 1 Hz. Contractile force was monitored continuously. Beta-adrenergic response, refractory period (RP) and maximum captured frequency (fmax) were assessed periodically. After cultivation, viability and electromechanical function were investigated, as well as the expression of several genes important for intracellular Ca2+ cycling and electrophysiology. Tissue microstructure was analyzed by confocal microscopy. We cultivated 19 constantly beating trabeculae from 8 patient samples for 12 days and 4 trabeculae from 3 specimen for 21 days. Functional parameters were compared directly after installation (0 d) with those after 12 d in culture. Contraction force was 384 ± 69 μN at 0 d and 255 ± 90 μN at 12 d (p = 0.8, n = 22), RP 480 ± 97 ms and 408 ± 78 ms (p = 0.3, n = 9), fmax 3.0 ± 0.5 Hz and 3.8 ± 0.5 Hz (p = 0.18, n = 9), respectively. Application of 100 nM isoprenaline to 11 trabeculae at 7 d increased contraction force from 168 ± 35 μN to 361 ± 60 μN (p < 0.01), fmax from 6.4 ± 0.6 Hz to 8.5 ± 0.4 Hz (p < 0.01) and lowered RP from 319 ± 22 ms to 223 ± 15 ms. CACNA1c (L-type Ca2+ channel subunit) and GJA1 (connexin-43) mRNA expressions were not significantly altered at 12 d vs 0 d, while ATP2A (SERCA) and KCNJ4 (Kir2.3) were downregulated, and KCNJ2 (Kir2.1) was upregulated. Simultaneous Ca2+ imaging and force recording showed preserved excitation-contraction coupling in cultivated trabeculae. Confocal microscopy indicated preserved cardiomyocyte structure, unaltered amounts of extracellular matrix and gap junctions. MTT assays confirmed viability at 12 d. We established a workflow that allows for stable cultivation and functional analysis of beating human atrial myocardium for up to 3 weeks. This method may lead to novel insights into the physiology and pathophysiology of human atrial myocardium.
CRIS-Team Scopus Importer:2022-03-25
Keywords: calcium imaging; confocal microscopy; gene expression; human atrium; in vitro; refractory period; tissue culture

Me2SO perfusion time for whole-organ cryopreservation can be shortened: Results of micro-computed tomography monitoring during Me2SO perfusion of rat hearts - Bleisinger, Nathalie; Dittrich, Ralf; Strahl, Olga; Brauweiler, Robert; Hoffmann, Inge; Beckmann, Matthias; Volk, Tilmann (PLoS ONE, 2020)
Cryopreservation of whole organs and specific tissues is an important and continually expanding field of medicine. The protocols currently used for organ preservation do not ensure survivability and functionality; the protocols for ovarian tissue lead to acceptable outcomes, but these are still capable of further improvement. In general, cryopreservation protocols need to be optimized. One important approach to improving cryopreservation protocols in general involves reducing exposure to cytotoxic cryoprotective agents prior to freezing. This study, therefore, evaluated the real-time tissue penetration of dimethyl sulfoxide, a cryoprotective agent that is widely used in cryopreservation. Dimethyl sulfoxide penetration in rat hearts perfused with a 15% (v/v) dimethyl sulfoxide solution was examined in real-time using dynamic contrast-enhanced micro-computed tomography imaging. Viability of cardiomyocytes was not significantly affected by the dimethyl sulfoxide perfusion procedure. Two different perfusion rates were evaluated and compared with perfusion using a common iodine-based contrast agent (iomeprol). The dynamic contrast-enhanced micro-computed tomography imaging data showed that dimethyl sulfoxide flushes both the extracellular and intracellular spaces in rat heart tissue to 95% equilibration after ≈ 35 s via perfusion. Subsequent wash-out via perfusion is completed to 95% within ≈ 49 s. The equilibration duration routinely used in dimethyl sulfoxide-based protocols for cryopreservation should therefore be questioned. Shorter incubation duration would perhaps be sufficient, as well as being beneficial in relation to cell survivability. It would be helpful to have techniques for non-invasive real-time monitoring of the penetration of cryoprotective agents and such techniques should be used to revise cryopreservation protocols. Switching to perfusion-based equilibration procedures might be beneficial, if feasible.
CRIS-Team Scopus Importer:2020-09-11

Microplegia in paediatric hearts - Münch, Frank; Kwapil, Nicola; Teske, Andreas; Rueffer, Andre; Dittrich, Sven; Volk, Tilmann; Purbojo, Ariawan (Perfusion-Uk, 2022)
Introduction A basic prerequisite for a good surgical outcome in heart surgery is optimal myocardial protection. However, cardioplegia strategies used in adult cardiac surgery are not directly transferable to infant hearts. Paediatric microplegia, analogous to Calafiore cardioplegia used in adult cardiac surgery, offers the advantage of safe myocardial protection without haemodilution. The use of concentration-dependent paediatric microplegia is new in clinical implementation. Material and methods Paediatric microplegia has been in clinical use in our institution since late 2014. It is applied via an 1/8 inch tube of a S5-HLM roller pump (LivaNova, Italy). As cardioplegic additive, a mixture of potassium (K) 20 mL (2 mmol/mL potassium chloride 14.9% Braun) and magnesium (Mg) 10 mL (4 mmol/mL Mg-sulphate Verla (R) i. v. 50%) is fixed into a syringe-pump (B. Braun, Germany). This additive is mixed with arterial patient blood from the oxygenator in different flow dependent ratios to form an effective cardioplegia. Technique After microplegia application of initially 25 mmol/L K with 11 mmol/L Mg for 2 min, a safe cardioplegic cardiac arrest is achieved, which after release of the coronary circulation, immediately returns to a spontaneous cardiac-rhythm. In the case of prolonged aortic clamping, microplegia is repeated every 20 min with a reduction of the application dose of K by 20% and Mg by 30% (20 mmol/L K; 8.5 mmol/L Mg) and a further reduction down to a maintenance dose (15 mmol/L K; 6 mmol/L Mg) after additional 20 min. The microplegia adapted to the needs of paediatric myocardium is convincing due to its simple technical implementation for the perfusionist while avoiding haemodilution. However, the required intraoperative interval of microplegia of approx. 20 min demands adapted intraoperative management from the surgeon.
CRIS-Team WoS Importer:2022-09-30

Progressive stretch enhances growth and maturation of 3D stem-cell-derived myocardium - Lu, Kun; Seidel, Thomas; Cao-Ehlker, Xiaochun; Dorn, Tatjana; Batcha, Aarif Mohamed Nazeer; Schneider, Christine Maria; Semmler, Marie; Volk, Tilmann; Moretti, Alessandra; Dendorfer, Andreas; Tomasi, Roland (Theranostics, 2021)
Bio-engineered myocardium has great potential to substitute damaged myocardium and for studies of myocardial physiology and disease, but structural and functional immaturity still implies limitations. Current protocols of engineered heart tissue (EHT) generation fall short of simulating the conditions of postnatal myocardial growth, which are characterized by tissue expansion and increased mechanical load. To investigate whether these two parameters can improve EHT maturation, we developed a new approach for the generation of cardiac tissues based on biomimetic stimulation under application of continuously increasing stretch. Methods: EHTs were generated by assembling cardiomyocytes derived from human induced pluripotent stem cells (hiPSC-CM) at high cell density in a low collagen hydrogel. Maturation and growth of the EHTs were induced in a custom-made biomimetic tissue culture system that provided continuous electrical stimulation and medium agitation along with progressive stretch at four different increments. Tissues were characterized after a three week conditioning period. Results: The highest rate of stretch (S3 = 0.32 mm/day) increased force development by 5.1-fold compared to tissue with a fixed length, reaching contractility of 11.28 mN/mm2. Importantly, intensely stretched EHTs developed physiological length-dependencies of active and passive forces (systolic/diastolic ratio = 9.47 ± 0.84), and a positive force-frequency relationship (1.25-fold contractility at 180 min-1). Functional markers of stretch-dependent maturation included enhanced and more rapid Ca2+ transients, higher amplitude and upstroke velocity of action potentials, and pronounced adrenergic responses. Stretch conditioned hiPSC-CMs displayed structural improvements in cellular volume, linear alignment, and sarcomere length (2.19 ± 0.1 µm), and an overall upregulation of genes that are specifically expressed in adult cardiomyocytes. Conclusions: With the intention to simulate postnatal heart development, we have established techniques of tissue assembly and biomimetic culture that avoid tissue shrinkage and yield muscle fibers with contractility and compliance approaching the properties of adult myocardium. This study demonstrates that cultivation under progressive stretch is a feasible way to induce growth and maturation of stem cell-derived myocardium. The novel tissue-engineering approach fulfills important requirements of disease modelling and therapeutic tissue replacement.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Biomechanics; Engineered heart tissue; Maturation; Progressive stretch; Stem-cell-derived myocardium

Rapid Pacing Decreases L-type Ca2+ Current and Alters Cacna1c Isogene Expression in Primary Cultured Rat Left Ventricular Myocytes - Ritzer, Anne; Röschl, Tobias; Nay, Sandra; Rudakova, Elena; Volk, Tilmann (Journal of Membrane Biology, 2023)
The L-type calcium current (ICaL) is the first step in cardiac excitation–contraction-coupling and plays an important role in regulating contractility, but also in electrical and mechanical remodeling. Primary culture of cardiomyocytes, a widely used tool in cardiac ion channel research, is associated with substantial morphological, functional and electrical changes some of which may be prevented by electrical pacing. We therefore investigated ICaL directly after cell isolation and after 24 h of primary culture with and without regular pacing at 1 and 3 Hz in rat left ventricular myocytes. Moreover, we analyzed total mRNA expression of the pore forming subunit of the L-type Ca2+ channel (cacna1c) as well as the expression of splice variants of its exon 1 that contribute to specificity of ICaL in different tissue such as cardiac myocytes or smooth muscle. 24 h incubation without pacing decreased ICaL density by 10% only. Consistent with this decrease we observed a decrease in the expression of total cacna1c and of exon 1a, the dominant variant of cardiomyocytes, while expression of exon 1b and 1c increased. Pacing for 24 h at 1 and 3 Hz led to a substantial decrease in ICaL density by 30%, mildly slowed ICaL inactivation and shifted steady-state inactivation to more negative potentials. Total cacna1c mRNA expression was substantially decreased by pacing, as was the expression of exon 1b and 1c. Taken together, electrical silence introduces fewer alterations in ICaL density and cacna1c mRNA expression than pacing for 24 h and should therefore be the preferred approach for primary culture of cardiomyocytes. Graphical Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-04-14
Keywords: Cacna1c; Cardiac memory; Regional differences; Remodeling

Region-specific mechanisms of corticosteroid-mediated inotropy in rat cardiomyocytes - Wacker, Caroline; Dams, Niklas; Schauer, Alexander; Ritzer, Anne; Volk, Tilmann; Wagner, Michael (Scientific Reports, 2020)
Regional differences in ion channel activity in the heart control the sequence of repolarization and may contribute to differences in contraction. Corticosteroids such as aldosterone or corticosterone increase the L-type Ca2+ current (ICaL) in the heart via the mineralocorticoid receptor (MR). Here, we investigate the differential impact of corticosteroid-mediated increase in ICaL on action potentials (AP), ion currents, intracellular Ca2+ handling and contractility in endo- and epicardial myocytes of the rat left ventricle. Dexamethasone led to a similar increase in ICaL in endocardial and epicardial myocytes, while the K+ currents Ito and IK were unaffected. However, AP duration (APD) and AP-induced Ca2+ influx (QCa) significantly increased exclusively in epicardial myocytes, thus abrogating the normal differences between the groups. Dexamethasone increased Ca2+ transients, contractility and SERCA activity in both regions, the latter possibly due to a decrease in total phospholamban (PLB) and an increase PLBpThr17. These results suggest that corticosteroids are powerful modulators of ICaL, Ca2+ transients and contractility in both endo- and epicardial myocytes, while APD and QCa are increased in epicardial myocytes only. This indicates that increased ICaL and SERCA activity rather than QCa are the primary drivers of contractility by adrenocorticoids.
CRIS-Team Scopus Importer:2020-07-24

Ryanodine Receptor Staining Identifies Viable Cardiomyocytes in Human and Rabbit Cardiac Tissue Slices - Pfeuffer, Ann-Katrin; Küpfer, Linda; Shankar, Thirupura S.; Drakos, Stavros G.; Volk, Tilmann; Seidel, Thomas (International Journal of Molecular Sciences, 2023)
In terms of preserving multicellularity and myocardial function in vitro, the cultivation of beating myocardial slices is an emerging technique in basic and translational cardiac research. It can be used, for example, for drug screening or to study pathomechanisms. Here, we describe staining for viable cardiomyocytes based on the immunofluorescence of ryanodine receptors (RyRs) in human and rabbit myocardial slices. Biomimetic chambers were used for culture and measurements of contractile force. Fixable fluorophore-conjugated dextran, entering cells with a permeable membrane, was used for death staining. RyRs, nuclei and the extracellular matrix, including the t-system, were additionally stained and analyzed by confocal microscopy and image processing. We found the mutual exclusion of the RyR and dextran signals in cultivated slices. T-System density and nucleus size were reduced in RyR-negative/dextran-positive myocytes. The fraction of RyR-positive myocytes and pixels correlated with the contractile force. In RyR-positive/dextran-positive myocytes, we found irregular RyR clusters and SERCA distribution patterns, confirmed by an altered power spectrum. We conclude that RyR immunofluorescence indicates viable cardiomyocytes in vibratome-cut myocardial slices, facilitating the detection and differential structural analysis of living vs. dead or dying myocytes. We suggest the loss of sarcoplasmic reticulum integrity as an early event during cardiomyocyte death.
CRIS-Team Scopus Importer:2023-09-15
Keywords: cardiac tissue slices; death staining; ryanodine receptor; sarcoplasmic reticulum; viability assay

Severe T-System Remodeling in Pediatric Viral Myocarditis - Fiegle, Dominik; Schober, Martin; Dittrich, Sven; Cesnjevar, Robert; Klingel, Karin; Volk, Tilmann; Alkassar, Muhannad; Seidel, Thomas (Frontiers in Cardiovascular Medicine, 2021)
Chronic heart failure (HF) in adults causes remodeling of the cardiomyocyte transverse tubular system (t-system), which contributes to disease progression by impairing excitation-contraction (EC) coupling. However, it is unknown if t-system remodeling occurs in pediatric heart failure. This study investigated the t-system in pediatric viral myocarditis. The t-system and integrity of EC coupling junctions (co-localization of L-type Ca2+ channels with ryanodine receptors and junctophilin-2) were analyzed by 3D confocal microscopy in left-ventricular (LV) samples from 5 children with myocarditis (age 14 +/- 3 months), undergoing ventricular assist device (VAD) implantation, and 5 children with atrioventricular septum defect (AVSD, age 17 +/- 3 months), undergoing corrective surgery. LV ejection fraction (EF) was 58.4 +/- 2.3% in AVSD and 12.2 +/- 2.4% in acute myocarditis. Cardiomyocytes from myocarditis samples showed increased t-tubule distance (1.27 +/- 0.05 mu m, n = 34 cells) and dilation of t-tubules (volume-length ratio: 0.64 +/- 0.02 mu m(2)) when compared with AVSD (0.90 +/- 0.02 mu m, p < 0.001; 0.52 +/- 0.02 mu m(2), n = 61, p < 0.01). Intriguingly, 4 out of 5 myocarditis samples exhibited sheet-like t-tubules (t-sheets), a characteristic feature of adult chronic heart failure. The fraction of extracellular matrix was slightly higher in myocarditis (26.6 +/- 1.4%) than in AVSD samples (24.4 +/- 0.8%, p < 0.05). In one case of myocarditis, a second biopsy was taken and analyzed at VAD explantation after extensive cardiac recovery (EF from 7 to 56%) and clinical remission. When compared with pre-VAD, t-tubule distance and density were unchanged, as well as volume-length ratio (0.67 +/- 0.04 mu m(2) vs. 0.72 +/- 0.05 mu m(2), p = 0.5), reflecting extant t-sheets. However, junctophilin-2 cluster density was considerably higher (0.12 +/- 0.02 mu m(-3) vs. 0.05 +/- 0.01 mu m(-3), n = 9/10, p < 0.001), approaching values of AVSD (0.13 +/- 0.05 mu m(-3), n = 56), and the measure of intact EC coupling junctions showed a distinct increase (20.2 +/- 5.0% vs. 6.8 +/- 2.2%, p < 0.001). Severe t-system loss and remodeling to t-sheets can occur in acute HF in young children, resembling the structural changes of chronically failing adult hearts. T-system remodeling might contribute to cardiac dysfunction in viral myocarditis. Although t-system recovery remains elusive, recovery of EC coupling junctions may be possible and deserves further investigation.
CRIS-Team WoS Importer:2021-02-19

Structural and Functional Assessment of Human Ventricular Myocardium - Abu-Khousa, M.; Fiegle, Dominik; Dendorfer, A.; Volk, Tilmann; Seidel, Thomas (ACTA PHYSIOLOGICA, 2019)
CRIS-Team WoS Importer:2019-11-12

The Degree of t-System Remodeling Predicts Negative Force-Frequency Relationship and Prolonged Relaxation Time in Failing Human Myocardium - Abu-Khousa, Maha; Fiegle, Dominik; Sommer, Sophie T.; Minabari, Ghazali; Milting, Hendrik; Heim, Christian; Weyand, Michael; Tomasi, Roland; Dendorfer, Andreas; Volk, Tilmann; Seidel, Thomas (Frontiers in Physiology, 2020)
The normally positive cardiac force-frequency relationship (FFR) becomes flat or negative in chronic heart failure (HF). Here we explored if remodeling of the cardiomyocyte transverse tubular system (t-system) is associated with alterations in FFR and contractile kinetics in failing human myocardium. Left-ventricular myocardial slices from 13 failing human hearts were mounted into a biomimetic culture setup. Maximum twitch force (F), 90% contraction duration (CD90), time to peak force (TTP) and time to relaxation (TTR) were determined at 37°C and 0.2–2 Hz pacing frequency. F1Hz/F0.5Hz and F2Hz/F0.5Hz served as measures of FFR, intracellular cardiomyocyte t-tubule distance (ΔTT) as measure of t-system remodeling. Protein levels of SERCA2, NCX1, and PLB were quantified by immunoblotting. F1Hz/F0.5Hz (R2 = 0.82) and F2Hz/F0.5Hz (R2 = 0.5) correlated negatively with ΔTT, i.e., samples with severe t-system loss exhibited a negative FFR and reduced myocardial wall tension at high pacing rates. PLB levels also predicted F1Hz/F0.5Hz, but to a lesser degree (R2 = 0.49), whereas NCX1 was not correlated (R2 = 0.02). CD90 correlated positively with ΔTT (R2 = 0.39) and negatively with SERCA2/PLB (R2 = 0.42), indicating that both the t-system and SERCA activity are important for contraction kinetics. Surprisingly, ΔTT was not associated with TTP (R2 = 0) but rather with TTR (R2 = 0.5). This became even more pronounced when interaction with NCX1 expression was added to the model (R2 = 0.79), suggesting that t-system loss impairs myocardial relaxation especially when NCX1 expression is low. The degree of t-system remodeling predicts FFR inversion and contraction slowing in failing human myocardium. Moreover, together with NCX, the t-system may be important for myocardial relaxation.
CRIS-Team Scopus Importer:2020-04-14
Keywords: cardiac excitation-contraction coupling; cardiac remodeling; force frequency relationship; heart failure; human heart; transverse tubular system

Transcriptional regulation of the L-type Ca2+ channel alpha C-1-subunit by corticosteroid - Ritzer, Anne; Rudakova, Elena; Volk, Tilmann (2017)
EVALuna2:214662

T-tubule loss in rat and human cardiomyocytes aggravates the effects of reduced SERCA activity on Ca2+ release - Fiegle, Dominik; Volk, Tilmann; Seidel, Thomas (ACTA PHYSIOLOGICA, 2022)
CRIS-Team WoS Importer:2022-10-07

Twenty-four hours preservation of hearts prior to cardiomyocyte isolation to reduce the number of experimental animals - Pfeilschifter, Benedikt; Seidel, Thomas; Volk, Tilmann (ACTA PHYSIOLOGICA, 2022)
CRIS-Team WoS Importer:2022-10-07